2017
DOI: 10.1016/s2352-3018(17)30128-5
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir 1200 mg once daily versus raltegravir 400 mg twice daily, with tenofovir disoproxil fumarate and emtricitabine, for previously untreated HIV-1 infection: a randomised, double-blind, parallel-group, phase 3, non-inferiority trial

Abstract: Merck & Co, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…A new formulation of RAL, 1200 mg QD, is now available for naïve patients and will make dosing easier [ 33 ] and improve adherence. Nevertheless, this strategy should be evaluated carefully, taking into account the virological failures reported with RAL 800 mg QD, and lack of efficacy due to historical genotypic mutations that can be archived from previous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A new formulation of RAL, 1200 mg QD, is now available for naïve patients and will make dosing easier [ 33 ] and improve adherence. Nevertheless, this strategy should be evaluated carefully, taking into account the virological failures reported with RAL 800 mg QD, and lack of efficacy due to historical genotypic mutations that can be archived from previous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the ONCEMRK phase 3 trial, raltegravir 1200 mg once daily (QD) showed noninferior efficacy to raltegravir 400 mg BID, with 88.9% and 88.3% of participants, respectively, achieving HIV-1 RNA <40 copies per milliliter at week 48. 10 In addition, the immunologic efficacy and overall safety profile of raltegravir QD were similar to those of raltegravir BID at week 48. Here, we report the long-term efficacy and safety of raltegravir 1200 mg QD compared with raltegravir 400 mg BID through week 96 of the ONCEMRK trial.…”
Section: Introductionmentioning
confidence: 74%
“…The noninferior efficacy and favorable safety profile of raltegravir 1200 mg QD were first demonstrated at week 48 and have been previously reported. 10 At week 96, the efficacy of raltegravir 1200 mg QD was again shown to be noninferior to that of raltegravir 400 mg BID, as assessed by the proportion of participants with HIV-1 RNA <40 copies per milliliter. Similar results were observed for the supportive virologic endpoint of HIV-1 RNA <50 copies per milliliter, and both treatment groups continued to show substantial increases in CD4 + T-cell counts (over 260 cells/mm 3 ) through week 96.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A subsequent pharmacokinetic‐pharmacodynamic response analysis indicated that lower trough concentrations in the once/day arm were associated with a lower virologic response . Following the results of the QDMRK study, ONCEMRK examined RAL in a new once/day formulation consisting of two 600‐mg tablets (total dose 1200 mg) given in combination with TDF/FTC in comparison with the standard 400‐mg twice/day regimen . Virologic response at 48 weeks was nearly identical between the two treatment groups (treatment difference 0.5% [95% CI −4.2 to 5.2]) despite markedly lower median trough concentration in the once/day regimen group.…”
Section: Methodsmentioning
confidence: 99%